How to Attract Health Workers to Rural Areas? Findings from a Discrete Choice Experiment from India - Rao, Krishna D.; Shroff, Zubin; Ramani, Sudha; Khandpur, Neha; Murthy, Seema; Hazarika, Indrajit; Choksi, Maulik; Ryan, Mandy; Berman, Berman; Vujicic, Marko (World Bank, Washington, DC, 2013)
India faces significant challenges in attracting qualified health workers to rural areas. In 2010 the authors conducted a Discrete Choice Experiment (DCE) in the Indian states of Uttarakhand and Andhra Pradesh to understand what health departments in India could do to make rural service more attractive for doctors and nurses. Specifically, we wanted to do the following: (a) examine the effect of monetary and nonmonetary job attributes on health worker job choices; and (b) develop incentive 'packages' with a focus on jobs in rural areas. The study sample included medical students, nursing students, in-service doctors and nurses at primary health centers. An initial qualitative study identified eight job attributes health center type, area, health facility infrastructure, staff and workload, salary, guaranteed transfer to city or town after some years of service, professional development, and job in native area. Respondents were required to choose between a series of hypothetical job pairs that were characterized by different attribute-level combinations. Bivariate probit and mixed logit regression was used for the statistical analysis of the choice responses. The findings suggest that the supply of medical graduates for rural jobs remained inelastic in the presence of individual monetary and nonmonetary incentives. In contrast, the supply of nursing students for rural jobs was elastic. Further, medical and nursing students from rural areas had a greater inclination to take up rural jobs. The supply of in-service doctors and nurses for rural posts was elastic. Higher salary and easier enrolment in higher education programs in lieu of some years of rural service emerged as the most powerful driver of job choice. Overall, better salary, good facility infrastructure, and easier enrolment in higher education programs appear to be the most effective drivers of uptake of rural posts for students and in-service workers. Combining these incentives can substantially increase rural recruitment. Incentivizing medical graduates to take up rural service appears to be challenging in India's context. This can be improved to some extent by offering easier admission to specialist training and recruiting students from rural backgrounds. In contrast, nursing students and in-services nurses are much more receptive to incentives for uptake of rural service. This suggests that cadres such as nurse practitioners can play an important role in delivering primary care services in rural India.